Influência da cura em autoclave na microestrutura, na resistência mecânica e na fotoatividade de recobrimento de TIO2 de materiais cimentícios - Dayana Cristina Silva Garcia (2019)
Cementitious materials are widely used in modern constructions. Heat treatment of cementitious materials is used in order to accelerate cement hydration and pozzolanic reaction and consequently improves mechanical properties at early age and durability of cement-based materials. Moreover, heat or hydrothermal treatment has been widely used for the crystallization of titania, and in this case, it is possible to create selfcleaning films on the surface of building materials. Heat treatment of cement-based materials is done in the oven, steam curing or under hydrothermal conditions (autoclave). Under hydrothermal conditions, C-S-H gel can convert to crystalline phases such as tobermorite and xonotlite and the autoclave curing allows the crystallization of titania under mild temperature. However, it is preferred to add pozzolanic materials to prevent α-C2SH formation. Therefore, the aim of this present work was to investigate the influence of autoclave curing in the microstructure and the mechanical properties of Portland cement-based materials and the photoactivity of TiO2 films. The samples were autoclaved under a 20 atm pressure for 8 hours at 220°C. The microstructure was characterized by elemental distribution X-ray maps, XRD, SEM, and FTIR. The mechanical properties such as hardness and elastic modulus of C-S-H and the compressive strength of the concrete were done. The results show that samples with a water-to-binder ratio of 0.20 and 30% of cement replacement exhibited the higher values of hardness and elastic modulus. The autoclave curing of concrete with UHPC mix proportion allowed the formation of C-S-H crystals, however, the heat treatment did not increase significantly the compressive strength. The Portland cement pastes with TiO2 films and autoclave curing exhibited a lower static contact angle.